2020
DOI: 10.3390/s20133692
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Biosensors Employing Natural and Artificial Heme Peroxidases on Semiconductors

Abstract: Heme peroxidases are widely used as biological recognition elements in electrochemical biosensors for hydrogen peroxide and phenolic compounds. Various nature-derived and fully synthetic heme peroxidase mimics have been designed and their potential for replacing the natural enzymes in biosensors has been investigated. The use of semiconducting materials as transducers can thereby offer new opportunities with respect to catalyst immobilization, reaction stimulation, or read-out. This review focuses on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 170 publications
0
17
0
Order By: Relevance
“…24,25 Peroxidase/peroxidase-mimic based H 2 O 2 sensors have also been developed and studied. 26,27 For example, an assay based on the oxidation of a chromogenic substrate using a horseradish peroxidase (HRP)/H 2 O 2 mixture is developed and the reaction sequence is usually evaluated by optical spectroscopy. Many different chromogenic substrates such as 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), ortho phenylenediamine (OPD), di-azo-aminobenzene (DAB) and 3,3′,5,5′-tetramethylbenzidine (TMB) were used in these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Peroxidase/peroxidase-mimic based H 2 O 2 sensors have also been developed and studied. 26,27 For example, an assay based on the oxidation of a chromogenic substrate using a horseradish peroxidase (HRP)/H 2 O 2 mixture is developed and the reaction sequence is usually evaluated by optical spectroscopy. Many different chromogenic substrates such as 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), ortho phenylenediamine (OPD), di-azo-aminobenzene (DAB) and 3,3′,5,5′-tetramethylbenzidine (TMB) were used in these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…They have wide potential practical applications as catalysts in biosensors, fuel-cell technology, environmental biotechnology, and medicine. [5][6][7][8][9][10][11][12] It has been shown that AEs mimic the activity of peroxidases, 5,[13][14][15] oxidases, 5,16 superoxide dismutases, 5,17 and hydrolases, 5,18 although only limited data were reported regarding reductase mimetics. [19][20][21][22][23][24][25] Natural reductases are the enzymes which belong to the E.C.…”
Section: Introductionmentioning
confidence: 99%
“…NZs possess increased stability and greater availability due to their simpler preparation technologies. Most reported NZs are mainly mimetics of oxidoreductases, including peroxidase (PO) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The main peculiarities of PO-like NZs as catalysts are that they have high stability, sensitivity, and selectivity to H 2 O 2 in extra-wide linear ranges. PO-like NZs coupled with natural oxidases are widely used in amperometric oxidase-based biosensors (ABSs) [1][2][3][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%